2012
DOI: 10.1590/s0004-27302012000400006
|View full text |Cite
|
Sign up to set email alerts
|

Treating primary hypothyroidism with weekly doses of levothyroxine: a randomized, single-blind, crossover study

Abstract: Objective: Compliance to levothyroxine treatment in hypothyroidism is compromised by daily schedule, and a weekly dose may be an alternative. Subjects and methods: This was a randomized, crossover study. Fourteen females were assigned to daily or weekly doses of LT4. After six weeks, they switched regimens. Thyroid parameters were measured at baseline, and after 42 and 84 days. Echocardiogram and hyperthyroidism symptoms were evaluated before and four hours after LT4 intake. Results: In the weekly dose treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
41
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(44 citation statements)
references
References 33 publications
2
41
1
Order By: Relevance
“…The thyroid function tests also continued to be within acceptable limits at all 3 follow up visits in both study arms, suggesting biochemical euthyroidism status with alternate day therapy. Our observations are similar to some earlier studies in older patients with hypothyroidism (6, 7). However due to financial constraints we could not estimate free T3 and free T4 levels which were measured by the previous investigators.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The thyroid function tests also continued to be within acceptable limits at all 3 follow up visits in both study arms, suggesting biochemical euthyroidism status with alternate day therapy. Our observations are similar to some earlier studies in older patients with hypothyroidism (6, 7). However due to financial constraints we could not estimate free T3 and free T4 levels which were measured by the previous investigators.…”
Section: Discussionsupporting
confidence: 93%
“…In addition, there is a strong evidence of auto regulation of peripheral conversion of thyroxine (T4) to triiodothyronine (T3) with increasing conversion rates at low serum T4 levels and decreasing conversion when T4 is elevated (5). Also, large doses of thyroxine are usually well tolerated (6-8). Together these properties suggest the possibility of using dosing intervals longer than the traditional 24 hours.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study on 14 patients, Bornschein et al [10] showed similar results and did not observe any hyperthyroidism during weekly therapy. A study done on Asian hypothyroid patients by Doraiswamy and Zainudin [11] demonstrated that after 3 months, there were no significant differences in thyroid profile between the weekly and daily groups.…”
Section: Discussionmentioning
confidence: 68%
“…pylori density, neutrophils, monocytes, atrophy, intestinal metaplasia (IM) in the antrum and corpus into one of five grades (0 to 4). Samples at grade 1 or more were considered positive . Furthermore, H .…”
Section: Participantsmentioning
confidence: 99%